PENGEMBANGAN BAHAN AJAR BERBASIS E-LEARNING EDMODO PADA MATERI KALOR DI SMP - Rahayu Utami; Fadillah Fadillah; Eny Enawaty (Universitas Tanjungpura, 2021)
AbstractThis research aims to describe the design of e-learning Edmodo-based teachingmaterials in heat materials in Junior High School and obtain data on validity andstudents’ response. The Research and Development method was used in this research.The development of e-learning Edmodo-based teaching materials follows the Design ofDick and Carey learning system. The development of e-learning Edmodo-basedteaching materials involved seventh grader of Pelita Cemerlang Junior High School asrespondents. Data was collected by direct communications, indirect communication,and documenter techniques. Questionnaire was used as data instrument in order todetermine the validity and students’ response toward the teaching materials. The resultof the research shows that the e-learning Edmodo-based teaching materials is “valid”with an average value of validity of 3.62 in material aspect, design aspect, languageaspect, and media aspect. Students’ response are “very good” with the acquisition ofscores of 3.18 in the one-on-one trial, small group tryout, and field trial.Keywords: e-learning Edmodo, teaching materials, heat, Dick and Carey